Kontribusi Variety Seeking Terhadap Brand Switching di Rocky Plaza Hotel Kota Padang - Restia Audina; Youmil Abrian; Waryono Waryono (JURNAL KAJIAN PARIWISATA DAN BISNIS PERHOTELAN, 2022)
This research originates from the results of pre-research observations of guests at Rocky Plaza Hotel Padang, where problems related to brand switching and variety seeking are still found that easily occur in the hospitality industry. The purpose of this research is to find out how much contribution variety seeking has on brand switching at Rocky Plaza Hotel Padang. This type of research is descriptive quantitative with a causal associative method which aims to measure how much influence variety seeking (X) has on brand switching (Y) at Rocky Plaza Hotel Padang. The population of this research is the guests of Rocky Plaza Hotel Padang, with a sample of 99 respondents using the purposive sampling method and the criteria for the respondent must have stayed more than once at Rocky Plaza Hotel and have stayed at four-star hotels in Padang City other than Rocky Plaza Hotel. Primary data is the data used in this research on these two variables obtained directly from guests using a questionnaire through the Google form as measured by a Likert scale whose validity and reliability tests have been tested. The results of this study: (1) variety seeking is in the unfavorable category (60.61%), (2) brand switching is in the sufficient category (53.54%), (3) the F value is obtained from the results of the regression hypothesis test simple linear is 83,538 with a sig level of 0.00 <0.05, therefore the variety seeking variable influences the brand switching variable by 46.3% and 53.7% is influenced by several other factors. From the results of the study, the proposed hypothesis is accepted, in this case there is a significant contribution between variety seeking and brand switching.